Molecular genotyping revealed the gene flow of Puccinia striiformis f. sp. tritici clonal lineage from Uzbekistan of Central Asia to Xinjiang of China - Muhammad Awais; Jinbiao Ma; Wenbing Chen; Bingbing Zhang; Khurshid S. Turakulov; Li Li; Dilfuza Egamberdieva; Meliev Sodir Karimjonovich; Zhensheng Kang; Jie Zhao (Phytopathology Research)
Abstract Wheat stripe rust, caused by Puccinia striiformis f. sp. tritici (Pst), is an air-borne fungal disease, and its spores can be spread far away from its origin to colonize in new territory, causing inter-regional epidemics. Xinjiang not only is an important and independent epidemic region from other stripe rust epidemiological regions in China but also has distinguished Pst genetic structure and spatial features. However, the inoculum source of the rust in Xinjiang has remained unknown. It is not clear whether inocula in Central Asian countries migrate to Xinjiang and whether mutual gene flows possibly occur between both regions. We conducted a comparative population study of Pst populations in Xinjiang and Uzbekistan to better understand the Pst migration pattern and inoculum source of the rust in Xinjiang. Our results revealed high genetic diversity in Xinjiang (0.86, 63 MLGs out of 207 samples), compared with the Uzbekistan population (0.76, 47 MLGs out of 255 samples). Our analyses uncovered the clear migration of Uzbekistan Pst populations to Northwest Xinjiang, which is in proximity to Central Asia. The migration of clonal lineage could cause genetic drift and potential threat changing the genetic structure and virulence pattern of Pst in China. Further studies need to be conducted in the Xinjiang region to understand and evaluate the behavior of foreign genotypes in the local environment and their overall impact on local wheat crops.